Sôfer mahîr : essays in honour of Adrian Schenker - Schenker, Adrian, 1939-; Goldman, Yohanan, 1952-; Kooij, Arie van der, 1945-; Weis, Richard D. (Supplements to Vetus Testamentum ;, 2006)
The essays that comprise this volume in honor of Adrian Schenker address a variety of issues and topics in the field of textual criticism and the textual history of the Hebrew Bible. Except for the Book of Kings, the contributors are editors of individual Biblical books for the new Biblia Hebraica Quinta . The topics of the essays range from assessments of the overall textual situation for a particular book to investigations of translation technique to studies of particularities in the Leningrad Codex and its Masorah. Most books of the Hebrew Scriptures are treated in one of the essays.